Design of an Electrolytic Cell for a Monolithic Photovoltaic-Electrolytic Hydrogen Generation System: The Electrode Aspects - Jeon, Hyo Sang; Kim, Jaehoon; Kim, Honggon; Lee, Sang Deuk; Min, Byoung Koun (TAYLOR & FRANCIS INC, 2012)
The combination of a photovoltaic (PV) and an electrolytic cell into one single system, a monolithic PV-electrolytic cell, has been suggested as an efficient solar hydrogen generation system. In this study, we demonstrate an efficient prototype electrolysis system applied to a monolithic PV-electrolytic cell. Specifically, the relatively large unit cell (active area of 36 cm(2)) used in the study made it possible to directly measure in volume the amount of hydrogen and oxygen generated. To enhance the activity of the electrodes we introduced channels, Co3O4 film, and Pt particles on stainless steel (SUS) substrates. The highest hydrogen production rate was obtained in the system in which Co3O4 electrocatalytic film on a SUS foil and Pt particles on a SUS plate with channels were used as an anode and a cathode, respectively.
Keywords: OXYGEN EVOLUTION; PHOTOELECTROCHEMICAL DEVICE; WATER; SOLAR